The pathogenesis of Niemann-Pick type C disease: a role for autophagy? - Pacheco, Chris D. (2008)
Niemann-Pick type C disease (NPC) is a sphingolipid storage disorder that results from inherited deficiencies of intracellular lipid trafficking proteins, and is characterized by an accumulation of cholesterol and glycosphingolipids in late endosomes and lysosomes. Patients with this disorder develop progressive neurological impairment that often begins in childhood, is ultimately fatal and is currently untreatable. How impaired lipid trafficking leads to neurodegeneration is largely unknown. Here we review NPC clinical features and biochemical defects, and discuss model systems used to study this disorder. Recent studies have established that NPC is associated with an induction of autophagy, a regulated and evolutionarily conserved process by which cytoplasmic proteins are sequestered within autophagosomes and targeted for degradation. This pathway enables recycling of limited or damaged macromolecules to promote cell survival. However, in other instances, robust activation of autophagy leads to cell stress and programmed cell death. We summarize evidence showing that autophagy induction and flux are increased in NPC by signaling through the class III-PI3K/Beclin-1 complex. We propose that an imbalance between induction and flux through the autophagic pathway contributes to cell stress and neuronal loss in NPC and related sphingolipid storage disorders, and discuss potential therapeutic strategies for modulating activity of this pathway.